Original illustrated tasks with photos of regional plants for botany knowledge control and consolidation - Klimenko, Mikhail; Tarasovskaya, Nataliya; Hamzina, Sholpan; Zhumadilov, Bulat; Zhumabekova, Bibigul (Institute of Advanced Engineering and Science, 2024)
This article addresses one of the current issues in education: the use of resources in biological disciplines classes that are required for students to develop meta-subject competencies. The incorporation of natural objects into educational content can create a favorable environment for teaching biology classes and assist students in developing necessary knowledge about regional flora. The authors created a set of integrated plant tasks that require knowledge of ecology, plant physiology, and evolution. The main goal of tasks is to learn about regional plant species and to control what you have learned. Certain activities are specifically created for hands-on engagement with nearby natural entities to determine their taxonomic classification, morphological characteristics, and adaptations. This approach, according to the authors, ensures productivity in biology teaching.